Dano existencial nas relações de emprego: paradoxos entre a responsabilidade civil do empregador e o trabalho excessivo em sobrejornada sob a ótica do TST - Regis, Pedro Gabriel de Medeiros (Universidade Federal Rural do Semi-Árido, 2016)
While the Federal Constitution of 1988 has protected the human dignity as its main principles, the growing pursuit for new activities, the greater demand for professional qualification by the market and the need to a basic standard of living has demanded more from the worker: there are increasing cases that the workers cannot have their own aim because they are totally linked to their work. The existential damage, in the context, arises when linked to the labor relations as a redress mechanism that is daily violated, and at this way, it repairs those damages that directly affect the life´s projects and the workers´ relations because of their behavior. However, its definition and the scope are still under development by the doctrine and the Brazilian case law which shapes the subject in a much more interesting way. This paper aims to confirm the legal landscape and its consequences over the new example of civil liability in a specific focus on overtime.
Artigo Acadêmico
Keywords: Dano existencial; Dignidade da pessoa humana; Responsabilidade civil; Trabalho em sobrejornada; CIENCIAS SOCIAIS APLICADAS::DIREITO